An assessment of the relationship between cervical vertebrae maturation index and eruption of permanent maxillary canines - D S Kothavade; R K Pandey; A Nagar (Wolters Kluwer Medknow Publications, 2012)
Aim : The purpose of the present study was to establish the relationship between the eruption of permanent maxillary canines and cervical vertebral maturation stages (CVMs) to assess an alternative method for determining time of canine eruption in the late mixed dentition. Materials and Methods : One hundred and twenty subjects with erupting permanent maxillary canines were observed both intraorally and radiographically with orthopantamograms. Lateral cephalograms were recorded to divide subjects according to CVM stage into prepeak (CS1 and CS2), peak (CS3 and CS4) and postpeak (CS5 and CS6) groups of puberty. Statistical Analysis : The differences between the prevalence rates of canine eruption in different groups of puberty were estimated using 'z test'. Results : Prepeak group comprised of forty six subjects, peak group sixty eight subjects and postpeak group six subjects. The differences in prevalence rates between peak and prepeak and between peak and postpeak groups were noticed highly significant (p<0.001), while prevalence rates between peak and postpeak was found less significant ( p0 <0.01). Conclusion : Eruption of the permanent maxillary canine can occur at any CVM stage till end of the puberty or after puberty (CS1-CS6). Thus, an absence of maxillary canine during or after postpeak stage of puberty (CS5 or CS6) suggests delayed eruption and canine impaction.